Структурно-функціональний аналіз системи управління кадровим потенціалом вищого навчального закладу - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д.; Воронюк, О. І. (Ways to Improve Construction Efficiency, 2014)
The results of structural and functional analysis of the human resources management of the university.